In vivo parasitological measures of artemisinin susceptibility. - Stepniewska, K; Ashley, E; Lee, S; Anstey, N; Barnes, K; Binh, T; D'Alessandro, U; Day, N; de Vries, P; Dorsey, G; Guthmann, J; Mayxay, M; et al. (2010)
Parasite clearance data from 18,699 patients with falciparum malaria treated with an artemisinin derivative in areas of low (n=14,539), moderate (n=2077), and high (n=2083) levels of malaria transmission across the world were analyzed to determine the factors that affect clearance rates and identify a simple in vivo screening measure for artemisinin resistance. The main factor affecting parasite clearance time was parasite density on admission. Clearance rates were faster in high-transmission settings and with more effective partner drugs in artemisinin-based combination treatments (ACTs). The result of the malaria blood smear on day 3 (72 h) was a good predictor of subsequent treatment failure and provides a simple screening measure for artemisinin resistance. Artemisinin resistance is highly unlikely if the proportion of patients with parasite densities of <100,000 parasites/microL given the currently recommended 3-day ACT who have a positive smear result on day 3 is <3%; that is, for n patients the observed number with a positive smear result on day 3 does not exceed (n + 60)/24.